A multicenter prospective study of 515 febrile neutropenia episodes in Argentina during a 5-year period - Parodi, Roberto Leandro (2019)
For better management of patients with febrile neutropenia, our study investigated the epidemiologic, microbiologic, and clinical characteristics of adult inpatients with febrile neutropenia and their mortality-associated factors. To this end, we carried out a prospective, observational, multicenter study in 28 Argentinian hospitals between 2007 and 2012. We included 515 episodes of febrile neutropenia from 346 patients, median age 49 years. Neutropenia followed chemotherapy in 77% of cases, half of the cases due to hematological malignancies. Most episodes were classified as high-risk according to MASCC criteria, and 53.6% of patients were already hospitalized at the onset of febrile neutropenia. Bloodstream infections were detected in 14% episodes; whereas an infectious source of fever was identified in 80% of cases. Mortality rate achieved to 14.95%. The binary regression analysis showed that persistence of fever at day 7, or neutropenia at day 14, dehydration and tachycardia at the onset of febrile neutropenia as well as prior infections were significantly associated with mortality. In addition to expanding our current knowledge on the features of adult patients with febrile neutropenia, present findings provide useful information for better management of them in Argentina, given the appropriate representativeness of centers participating in the study.